Capital, competition and stability nexus in the Kenya banking sector - Samuel Kiemo (Kenya Bankers Association (KBA), 2025)
The paper examines the nexus between capital, competition and stability in the Kenya banking sector. This is achieved by applying a panel data analysis model on annual bank level data for the period 2001 to 2022. The paper estimated H-Statistics and Bank Stability Index to measure evolution of banking sector competition and stability respectively. The results revealed four key findings. First, Kenya banking sector competition conditions is monopolistic with few large banks dominating. Secondly, on average the banking sector remains stable, with considerable gain in long-term resilience. Thirdly, increase in capital promotes competition first, however significant increase in capital reduces competition. Fourth, increase in capital promotes banking sector stability. The paper concludes that, capital positively effects both banking sector competition and stability. However, significant increase in bank capital reduce competition. The paper recommends appropriate capital regulation reforms should be implemented taking cognizance of the adverse implication on significant increase in capital on banking sector competition.
Keywords: 330; Capital; Competition; Stability; Panel